Analytical Study on the Development of Meaning in Tafsir Jalalain of Surah Al-Mu’minun by Gus Yahya Cholil Staquf on YouTube from the Perspective of J.E. Gracia - Rosyida Amalia; Salamah Noorhidayati; Ahmad Zainal Abidin (Universitas Darussalam Gontor, 2025)
This study discusses the development of interpretative meaning in the Qur’anic exegesis carried out by Gus Yahya Cholil Staquf, with a specific focus on Surah Al-Mu’minun verse 6. The central focus of this research lies in how Gus Yahya, in addition to his role as a national political figure, actively contributes to Qur’anic interpretation through his teachings delivered to students at the Raudlatut Thalibin Islamic Boarding School in Rembang. These tafsir sessions are broadcast live via the Gus Mus Channel on YouTube, serving as an important medium for disseminating Islamic thought and Qur’anic interpretations to the broader public. This study aims to examine the form of meaning development applied by Gus Yahya Cholil Staquf in interpreting QS. Al-Mu’minun:6 and to analyze the implications of that meaning development for Qur’anic interpretation in the contemporary era. The method used is descriptive-analytical with a library research approach. The primary source of this research is the recorded tafsir sessions of Tafsir Jalalain by Gus Yahya on the Gus Mus Channel, while secondary sources include relevant books, journals, and scholarly references. The findings reveal that there are three main functions in the development of meaning in Gus Yahya’s interpretation of QS. Al-Mu’minun verse 6, first, the historical function, which highlights that the phrase mā malakat aymānuhum previously referred to the practice of owning female slaves; Second, the meaning development function, which reflects efforts to recontextualize the phrase to align with contemporary legal and social values, such as lawful relationships through marriage; and Third, the implicative function, which emphasizes the verse’s social and ethical significance in shaping individual moral awareness and preserving sexual integrity in modern society. The main contribution of this study lies in how Gus Yahya’s contextual interpretation serves as a bridge between classical meanings and universal human values in the modern era. As such, this research offers a significant contribution to grounding the Qur’an as a text that remains relevant and transformative amid the challenges of contemporary times.